High levels of copper and zinc supplementation in broiler diets on growth performance, carcase traits and apparent ileal mineral absorption - Santos, T. S. dos [UNESP]; Augusto, K. V.Z.; Han, Y.; Sartori, M. M.P. [UNESP]; Denadai, J. C. [UNESP]; Santos, C. T. [UNESP]; Sobral, N. C. [UNESP]; Roça, R. O. [UNESP]; Sartori, J. R. [UNESP] (Taylor & Francis, 2021)
1. This study investigated the effects of hydroxy trace minerals (HTM) compared to sulphate trace minerals (STM) supplementation on growth performance, carcase parameters and mineral retention in broilers. 2. A total of 1792 male Cobb 500 d-old were allocated in a completely randomised trial design to one of eight dietary treatments with eight replicates per treatment. The HTM sources used were two levels of Cu hydroxychloride (CHC) (low and high), combined with three levels of Zn hydroxychloride (ZHC) (low, med and high) and two additional treatments STM; Cu sulphate monohydrate (CSM) (low and high) combined with high Zn sulphate monohydrate (ZSM). At 21 and 42 d-old growth performance was evaluated. Additionally, at 42 d-old the carcase traits, meat quality, apparent ileal absorption and activity of antioxidant enzymes were accessed. 3. A data showed that broilers receiving high-CHC had higher body weight, weight gain and better feed conversion ratio as compared to low-CHC at 21 d-old. On day 42, the feed conversion ratio was improved for birds supplemented with high-CHC in diets containing med-ZHC, as compared to low-CHC. 4. Dietary Cu increased the redness of breast colour at the level of high-CHC compared to low-CHC. Greater results were observed on carcase traits for the med-ZHC group as compared to low- or high-ZHC. The ceruloplasmin activity in serum increased in the high-CSM diets containing high-ZSM as compared to low-CSM. The AIA of Cu was higher in broilers supplemented with high-CHC containing med-ZHC as compared to low-CHC. Otherwise, the AIA of Zn increased in broilers fed low-CHC containing low- or med-ZHC as compared to high-CHC. 5. The trial showed that mineral trace supplementation of broilers diets with high-CHC (150 mg/kg) and low-ZHC (80 mg/kg) was a good alternative to replace sulphate mineral sources in diets.
Keywords: Bond strength; carcase yield; Cu; feed conversion ratio; mineral source; Zn